Economic Analysis of the Impact of Overseas and Domestic Treatment and Screening Options for Intestinal Helminth Infection among US-Bound Refugees from Asia. - Brian Maskery; Margaret S Coleman; Michelle Weinberg; Weigong Zhou; Lisa Rotz; Alexander Klosovsky; Paul T Cantey; LeAnne M Fox; Martin S Cetron; William M Stauffer (Public Library of Science (PLoS), 2016)
BACKGROUND:Many U.S.-bound refugees travel from countries where intestinal parasites (hookworm, Trichuris trichuria, Ascaris lumbricoides, and Strongyloides stercoralis) are endemic. These infections are rare in the United States and may be underdiagnosed or misdiagnosed, leading to potentially serious consequences. This evaluation examined the costs and benefits of combinations of overseas presumptive treatment of parasitic diseases vs. domestic screening/treating vs. no program. METHODS:An economic decision tree model terminating in Markov processes was developed to estimate the cost and health impacts of four interventions on an annual cohort of 27,700 U.S.-bound Asian refugees: 1) "No Program," 2) U.S. "Domestic Screening and Treatment," 3) "Overseas Albendazole and Ivermectin" presumptive treatment, and 4) "Overseas Albendazole and Domestic Screening for Strongyloides". Markov transition state models were used to estimate long-term effects of parasitic infections. Health outcome measures (four parasites) included outpatient cases, hospitalizations, deaths, life years, and quality-adjusted life years (QALYs). RESULTS:The "No Program" option is the least expensive ($165,923 per cohort) and least effective option (145 outpatient cases, 4.0 hospitalizations, and 0.67 deaths discounted over a 60-year period for a one-year cohort). The "Overseas Albendazole and Ivermectin" option ($418,824) is less expensive than "Domestic Screening and Treatment" ($3,832,572) or "Overseas Albendazole and Domestic Screening for Strongyloides" ($2,182,483). According to the model outcomes, the most effective treatment option is "Overseas Albendazole and Ivermectin," which reduces outpatient cases, deaths and hospitalization by around 80% at an estimated net cost of $458,718 per death averted, or $2,219/$24,036 per QALY/life year gained relative to "No Program". DISCUSSION:Overseas presumptive treatment for U.S.-bound refugees is a cost-effective intervention that is less expensive and at least as effective as domestic screening and treatment programs. The addition of ivermectin to albendazole reduces the prevalence of chronic strongyloidiasis and the probability of rare, but potentially fatal, disseminated strongyloidiasis.